The image of the Balkans in Eusebius’ „Chronicle” - Kotłowska, Anna (Balcanica Posnaniensia. Acta et studia, 2011)
The article analyzes the representation of the Balkans in the Chronicle of Eusebius of Caesarea, one of the most important works of early Christian historiography. The author points out that the Balkan region occupies only a marginal place in Eusebius’s work — out of more than 1,200 entries, only about twenty refer to the Balkans, most often indirectly. The aim of the article is to reconstruct the image of the Balkans in Eusebius’s narrative and to analyze the functions fulfilled by references to the Thracians, Illyrians, and Macedonia. The author employs source analysis and comparative methods, confronting the entries in the Chronicle with Greek and Byzantine traditions. The article demonstrates that Eusebius perceived the Balkans mainly through the prism of mythology, political history, and the idea of thalassocracy, while information about the region served the construction of a universal vision of history. The results of the analysis indicate that despite the small number of references, the Balkans played an important role as an element of the narrative about the continuity of Mediterranean civilization and the imperial order of the world.